1994
DOI: 10.1093/oxfordjournals.aje.a117031
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Inorganic Arsenic and Prevalence of Diabetes Mellitus

Abstract: To examine the association between ingested inorganic arsenic and prevalence of diabetes mellitus, in 1988, the authors studied 891 adults residing in villages in southern Taiwan where arseniasis is hyperendemic. The status of diabetes mellitus was determined by an oral glucose tolerance test and a history of diabetes regularly treated with sulfonylurea or insulin. The cumulative arsenic exposure in parts per million-years was calculated from the detailed history of residential addresses and duration of drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
204
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(218 citation statements)
references
References 0 publications
12
204
1
1
Order By: Relevance
“…This study confirmed the findings of our previous study (Lai et al 1994) in which the subjects in the arseniasis-endemic area had an elevated prevalence of diabetes compared with the nonendemic area (odds ratio = 2.7 after adjustment for age and sex). In this study we found that women tended to have a higher prevalence of diabetes than did men in the arseniasis-endemic area but not in the nonendemic area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirmed the findings of our previous study (Lai et al 1994) in which the subjects in the arseniasis-endemic area had an elevated prevalence of diabetes compared with the nonendemic area (odds ratio = 2.7 after adjustment for age and sex). In this study we found that women tended to have a higher prevalence of diabetes than did men in the arseniasis-endemic area but not in the nonendemic area.…”
Section: Discussionsupporting
confidence: 91%
“…The associations between long-term exposure to arsenic and microvascular diseases, including renal disease, retinopathy, and neuropathy, remain to be elucidated. Epidemiologic studies have shown a dose-response relationship between arsenic in drinking water and prevalence and mortality of diabetes mellitus in southwestern Taiwan (Lai et al 1994;Tsai et al 1999). Similar findings have been reported in Sweden , Bangladesh (Rahman et al 1998), and the United States (Lewis 1999).…”
mentioning
confidence: 99%
“…In addition to the increased health risks presented above, two research groups suggest that there may be associations between very high arsenic exposure and diabetes mellitus (Lai et al, 1994;Rahman and Axelson, 1995). This risk assessment survey identifies arsenic as a potential problem in some Arizona communities.…”
Section: Discussionmentioning
confidence: 86%
“…Previous research of the effects of chronic exposure to iAs has focused primarily on its carcinogenic potential. However, chronic exposures to iAs from the environment or in occupational settings have also been linked to non-carcinogenic diseases, including peripheral vascular disease, cardiovascular and cerebrovascular diseases Chen et al, 1996;Chiou et al, 1997;Engel et al, 1994;Thomas and Goyer, 1995;Tseng et al, 1995;Tseng et al, 1997), hypertension , goiter (Chang et al, 1991), hepatomegaly (Santra et al, 1999), respiratory system dysfunction (Mazumder et al, 2000), nervous system dysfunction (Bencko et al, 1977;Chisolm Jr. and Thomas, 1983;Masahiko and Hideyasu, 1973), and diabetes mellitus (Lai et al, 1994;Rahman et al, 1998;Rahman et al, 1999;Tseng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%